Re-imagining Research: A Bold Call, but Bold Enough?; Comment on “Experience of Health Leadership in Partnering with University-Based Researchers in Canada: A Call to ‘Re-Imagine’ Research” - Bev J. Holmes (International Journal of Health Policy and Management, 2020)
Many articles over the last two decades have enumerated barriers to and facilitators for evidence use in health systems. Bowen et al’s article “Response to Experience of Health Leadership in Partnering with University-Based Researchers: A Call to ‘Re-imagine Research’” furthers the debate by focusing on an under-explored research area (health system design and health service organization) with an under-studied stakeholder group (health system leaders), by undertaking a broad program of research on partnerships, and, based on participant responses, by calling for re-imagining of research itself. In response to the claim that the research community is not providing expertise to this pressing issue in the health system, I provide four high level reasons: partnerships mean different things to different people, our language does not reflect the reality we want, our health systems have yet to fully embrace evidence use, and complexity is easier to talk about than act within. Bowen et al’s study, and their broader program of research, is well-placed to explore these issues further, helping identify appropriate researcher-health system leader partnership models for various health system change projects. Given the positive shifts identified in this study, and the knowledge that participants demonstrate about what needs to change, the time is right for bold action, re-imagining not only research, but healthcare, such that the production and use of evidence for better health is embraced and supported.